Search for chromosome rearrangements: New approaches toward discovery of novel translocations in head and neck squamous cell carcinoma. Issue 6 (17th July 2012) - Wang, Vivian W.; Laborde, Rebecca R.; Asmann, Yan W.; Li, Yang; Ma, Jian; Eckloff, Bruce W.; Tombers, Nicole M.; Olsen, Steven M.; Moore, Eric J.; Olsen, Kerry D.; Smith, David I.
Abstract Background Chromosome rearrangements that result in gene fusions have important roles in the initial steps of tumorigenesis, especially in leukemias and lymphomas, but the biological and clinical impact of gene fusions in common solid tumors are less understood. The purpose of this study was to discover novel translocations that could result in gene fusions in oropharyngeal squamous cell carcinomas (OPSCCs). Methods Translocations were identified using 2 different bioinformatics pipelines, SnowShoes‐FTD and FusionHunter, examining data from 11 paired‐end RNA sequencing (RNA‐Seq) data in OPSCC. Translocations were validated by RT‐PCR and Sanger sequencing analysis. Results Two novel cancer‐specific translocations involving MGST3‐ZMAT5 and MS4A7‐C2CD3 were found in 2 of the tumor samples tested. However, these translocations were found only in the single tumor. Conclusions We hope that this integrative methodology will elucidate key aspects of tumor biology as well as generate novel targets for cancer diagnoses and therapies. Head Neck, 2012